Why Sub-Saharan Africa Lags in Electronic Health Record (EHR) Adoption and Possible Strategies to Increase EHR Adoption in this Region - Odekunle, Florence Femi; Srinivasan, Shankar; Odekunle, Raphael Oluseun (Journal of Health Informatics in Africa, 2018)
Poor health information system has been identified as a major challenge in healthcare in many developing countries including sub-Saharan African countries. EHR has been shown as an important tool to improve access to patient information with attendance improved quality of care. However, EHR has not been widely implemented/adopted in sub-Saharan Africa. Therefore, this study seeks to identify factors that affect the adoption of an EHR in sub-Saharan Africa and strategies to improve its adoption in this region. A literature review was conducted using one of the second generation approaches, mixed synthesis. A comprehensive literature search was conducted on two electronic databases: PubMed and Medline. The available evidence indicates that there are many factors that hinder widespread adoption of an EHR in sub-Saharan Africa. These include high costs of procurement and maintenance of the EHR system, lack of financial incentives and priorities, poor electricity supply and internet connectivity, and primary user’s limited computer skills. However, strategies such as implementation planning, financial supports, appropriate EHR system selection, training of primary users and the adoption of the phased implementation process have been identified to facilitate the use of an EHR. Wide adoption of an EHR in sub-Saharan Africa region requires a lot more effort than we think because of the current poor level of technological development, lack of required computer skills, and limited resources.